PENGARUH PARTISIPASI MASYARAKAT DAN SISTEM KEUANGAN DESA (SISKEUDES) TERHADAP KEBERHASILAN PENGELOLAAN DANA DESA DI DESA KRASAK - Dewi Kartika; Krisdiyawati; Azarine Sava Vania Slamet (Universitas Sulawesi Barat, 2021)
This study aims to determine the Participation of The Village Community and Financial System to the Success of Village Fund Management in Krasak Village, Brebes Regency. Research methodology through data collection with questionnaire survey techniques to respondents and sampling using slovin formula. The data analysis techniquein this study used multiple linear regression analysis with the help of SPSS version 22. The results of this study showed that the variables of community participation had a partial significant effect on the success of village fund management, the variable use of the village financial system had a significant partial effect on the success of village fund management and community participation and the village financial system simultaneously influenced the success of village fund management Keywords: Success of Village Fund Management, Community Participation, Siskeudes